Decubitus Risk Assessment Instruments in ICU Patients: Literature Review - Deni Supriyanti; Dwi Retno Sulistyaningsih; Indah Sri Wahyuningsih; Dwi Happy Rochmawati (Indonesian Journal of Global Health Research, 2025)
Pressure ulcers can cause various problems for clients and hospitals. For patients, decubitus can cause extreme pain and discomfort, increase the length of stay (LOS), and quality indicators in the hospital cannot be achieved. The chronology of various factors means that a less standard decubitus assessment instrument will cause decubitus to continue to occur. This study aims to analyze the instruments used to prevent pressure ulcers in ICU patients. This study reviews eight relevant articles from 2019-2024. The results of a literature search of 2,662 journals resulted in a total of 15 journals being reviewed with the results of several studies using different pressure ulcer prevention instruments, including the Braden Scale, PUPrep, PUP Instrument, PIPGAI, COMHON, CFA, VALENT, PUKAT, KPUP, and RAPS, all instruments are used as decubitus detection instruments.